How Social-Relational Context Impacts the Mental Health of Adolescent and Young Adults Living with and Without HIV in Mozambique: A Social Network Analysis Study - Roberto Benoni; Anna Sartorello; Chiara Malesani; Hamilton Cardoso; Izilda Chaguruca; Moisés Domingos Sande Matope; Giovanni Putoto; Carlo Giaquinto; Michela Gatta (Journal of Epidemiology and Global Health)
Abstract Purpose This study aims to describe the social-relational context of adolescents and young adults living with (AYALHIV) and without HIV (AYAHIV-) in the city of Beira (Mozambique) and to assess how it can impact their mental health. Methods A cross-sectional study with three-level assessment was conducted between July and August 2023. Socio-economic factors were assessed through an ad-hoc questionnaire, mental health through symptom Checklist-90 (SCL-90), and social-relational networks using social network analysis (SNA). SNA parameters included were: average degree centrality, closeness centrality, betweenness centrality, eigenvector centrality and transitivity. Robust linear regression model was used to assess association between SNA parameters and SCL-90 scores. Results AYAs involved were 352 (F: 50.7%) and 341 (96.9%) completed both sociogram and SCL-90. Average degree centrality was 1.44 (SD 0.77) for supportive networks (supSN) and 0.49 (SD 0.39) for stressful ones (strSN). The average degree centrality was higher in AYAHIV- compared to AYALHIV (0.009). Supportive edges occurred more often between the individual and their mother (65.1%), while stressful edges between one (24.3%) or two (18.8%) neighbourhood people. The supSN betweenness was 0.27 (SD 0.24) in females and was significantly lower compared to males (0.33, SD 0.27, p = 0.017). The mean score at the SCL-90 was 1.1 (SD 0.5). An increase in 1 SD of the average degree centrality of the supSN was associated with a decrease of 0.14 SD at the SCL-90 (p = 0.014). The SCL-90 score was significantly lower in males (p = 0.045) and in AYAs from the high socio-economic group (p = 0.009). Conclusion Two groups proved to be more vulnerable with regard to socio-relational networks, women and AYALHIV. Better interconnected social support networks were associated with better mental health (i.e. lower scores on the SCL-90). Improving support within the community is therefore important for achieving better mental well-being for all.